2017
DOI: 10.1111/imm.12832
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cells at the interface between obesity and asthma

Abstract: SummaryObesity and asthma prevalence has dramatically and concomitantly increased over the last 25 years, and many epidemiological studies have highlighted obesity as an important risk factor for asthma. Although many studies have been performed, the underlying mechanisms remain poorly understood. Innate mechanisms have been involved in both diseases, in particular through the recently described innate lymphoid cells (ILCs). ILCs are subdivided into three groups that are defined by their cytokine production an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 127 publications
(229 reference statements)
0
26
0
1
Order By: Relevance
“…Similarly, we also observed reduced levels of the innate Th2 cell-promoting cytokine IL-33, and the adipokine, leptin in the lungs of dams fed a high fat diet that were pregnant twice. Interestingly, increased expression of these mediators has been shown to promote asthma exacerbation and airway hyper-reactivity in animal models [47]. Furthermore, reduced tissue elastance (and adiponectin levels in BALF) was observed in the offspring of the second pregnancy of dams fed either diet; suggesting that there may be protective effects of a second pregnancy that extend to the offspring in some developmental niches (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we also observed reduced levels of the innate Th2 cell-promoting cytokine IL-33, and the adipokine, leptin in the lungs of dams fed a high fat diet that were pregnant twice. Interestingly, increased expression of these mediators has been shown to promote asthma exacerbation and airway hyper-reactivity in animal models [47]. Furthermore, reduced tissue elastance (and adiponectin levels in BALF) was observed in the offspring of the second pregnancy of dams fed either diet; suggesting that there may be protective effects of a second pregnancy that extend to the offspring in some developmental niches (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Very often, although not always, the level of leptin in patients with obesity is increased, and the level of adiponectin is reduced [ 7 , 8 ]. It was shown that the administration of leptin to BALB/c mice increased the intensity of allergic inflammation and production of IgE while the administration of adiponectin inhibited it [ 8 10 ]. It is especially important to note that adipose tissue contains TLSs, although their number varies depending on the anatomical location [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chronic inflammation that results from high levels of adiposity is associated with the development of a number of inflammatory conditions, mediated in part through profound effects of adipokines on a broad range of immune cells, including dendritic cells, innate lymphoid cells, and neutrophils . This new understanding of how mast cells respond to leptin and adiponectin adds another piece to this puzzle.…”
mentioning
confidence: 99%